The Centrality of the State in Neoliberal Times - Mayo, Peter (International Gramsci Journal, 2023)
One of the greatest myths being propagated in this contemporary neoliberal scenario is that the nation state is no longer the main force in this period characterized by the intensification of globalization. Deregulation was brought in by governments to expedite the process where various forms of provision, private and formerly public, were left to the market. And yet the credit crunch starkly laid bare the folly of this conviction as new forms of regulation are being put in place with the state, the national state, intervening to bail out banks and other institutions in this situation. I consider this an opportune moment to look at the function of the state and assess its role within the contemporary scenario of ‘hegemonic globalization’, to adopt the term used by the Portuguese sociologist, Boaventura de Sousa Santos (de Sousa Santos in Dale and Robertson, 2004: 151), and its underlying ideology, neoliberalism. I will look at different theoretical insights and then end this excursus with a discussion of Gramsci’s conceptualization of the state and its implications for present day politics.